Development of web based project monitoring system (PMS) using MVC design pattern / Fadzilah Talib - Talib, Fadzilah (2014)
This thesis research mainly focus on the development of Web Based Project Monitoring System (PMS) using MVC Design Pattern for Dynareka Sdn Bhd. It studies the development of a web-based using MVC design pattern which help researchers in better understanding about MVC Design Pattern where it separate an application into three major components which are; models that includes the main functionality, views that represent the user interface and controllers that control the updates to views. The benefit of MVC design pattern it also helps the developer to write code in better organized, maintainable and this pattern extensively tested over multiple languages and generations of programmers. Basically this thesis research has three objectives that need to be achieved. The first objective is to identify and analyze the requirements for PMS. The second and third objectives are to design the PMS based on MVC design pattern and to develop PMS based on MVC design pattern. This thesis research as a solution to the problems occurs in project monitoring especially in preparing progress report to the clients. By providing PMS, users can monitor the project progress easily and help to manage the information involved during the project monitoring. As the result, this project helps to increase the quality of project monitoring activities ,client satisfaction and for system enhancement, it also help the future developer be more understanding on the design and development phase in this system because the MVC design pattern is applied on those phases. However, some enhancement on Project Monitoring System is needed such as providing the intelligent Project Dashboard, notification email to the client, enhance PMS to mobile version and others to ensure PMS able in providing better services and also be more effective and interactive webpage.